Direct Determination of Cu, Cd, Ni and Pb in Aquatic Humic Substances by Graphite Furnace Atomic Absorption Spectrometry - de Oliveira, Adriana P.; Villa, Ricardo D.; Goveia, Danielle. [UNESP]; Lobo, Fabiana A.; Rosa, André H. [UNESP] (Bentham Science Publishers, 2011)
A method has been developed for the direct determination of Cu, Cd, Ni and Pb in aquatic humic substances (AHS) by graphite furnace atomic absorption spectrometry. AHS were isolated from water samples rich in organic matter, collected in the Brazilian Ecological Parks. All analytical curves presented good linear correlation coefficient. The limits of detection and quantification were in the ranges 2.5-16.7 μg g-1 and 8.5-50.0 μg g-1, respectively. The accuracy was determined using recovery tests, and for all analytes recovery percentages ranged from 93-98%, with a relative standard deviation less than 4%. The results indicated that the proposed method is a suitable alternative for the direct determination of metals in AHS. © 2011 Bentham Science Publishers Ltd.
Keywords: Ahs; Direct determination; Gfaas; Metals